2018
DOI: 10.1007/s00482-018-0345-z
|View full text |Cite
|
Sign up to set email alerts
|

Validierung der deutschen Übersetzung des Injustice Experience Questionnaire (IEQ) in 5 ambulanten Schmerzbehandlungseinrichtungen

Abstract: Schlussfolgerung: Die Analysen attestieren der deutschen Übersetzung des IEQ ausgezeichnete psychometrische Eigenschaften. Somit liegt mit der deutschsprachigen Version des IEQ ein validierter Fragebogen zum Screening auf wahrgenommene Ungerechtigkeit vor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The IEQ has proven to be a good predictor for delayed healing in patients experiencing pain and post-traumatic stress (6,74,75). However, we are unaware of the use of this questionnaire in the OFP domain, except for its German-language validation (28). Notably, patients perceiving injustice also had pain for a longer duration compared to subjects with lower IEQ scores (r = 0.27; P < 0.001).…”
Section: Correlations Between Pain and Well-being Scoresmentioning
confidence: 99%
“…The IEQ has proven to be a good predictor for delayed healing in patients experiencing pain and post-traumatic stress (6,74,75). However, we are unaware of the use of this questionnaire in the OFP domain, except for its German-language validation (28). Notably, patients perceiving injustice also had pain for a longer duration compared to subjects with lower IEQ scores (r = 0.27; P < 0.001).…”
Section: Correlations Between Pain and Well-being Scoresmentioning
confidence: 99%
“…In validating our Hebrew version of the IEQ, we confirmed a 1-factor structure for all 12 items with excellent reliability. Previous validations and translations of the IEQ have yielded mixed results regarding a 2-factor [64][65][66]69 versus 2-factor 19,67,68 structure, although the latter consistently reports very high overlap between the components. As such, our findings support Sullivan et al's 7 original conception that the IEQ might be best construed as a complex but unitary construct, with the theoretical subscales not deriving statistically separate components.…”
Section: Discussionmentioning
confidence: 98%
“…To test the structural validity, we conducted a factor analysis using Principal Component Analysis (PCA) with oblique (direct oblimin) rotation. Although some validations of the IEQ have employed Confirmatory Factor Analysis, 64,68,69 we opted for PCA in line with the many other IEQ validation studies. 7,19,[65][66][67] Given the varied findings of factor analyses within these papers, we concluded that the more exploratory PCA was preferable to a confirmatory method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations